2008
DOI: 10.1128/jb.01002-08
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Contribution of theLegionella pneumophila lqsGenes to Pathogen-Host Interactions

Abstract: The causative agent of Legionnaires' disease, Legionella pneumophila, is a natural parasite of environmental protozoa and employs a biphasic life style to switch between a replicative and a transmissive (virulent) phase. L. pneumophila harbors the lqs (Legionella quorum sensing) cluster, which includes genes encoding the autoinducer synthase LqsA, the sensor kinase LqsS, the response regulator LqsR, and a homologue of HdeD, which is involved in acid resistance in Escherichia coli. LqsR promotes host-cell inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 75 publications
1
69
0
Order By: Relevance
“…2A and B, respectively). It should be noted that FleR and LqsR were previously suggested to be involved in flagellum gene expression (57,58) and that LqsR was also suggested to be involved in the regulation of effector-encoding genes (58). These results show that, in addition to directly contributing to the regulation of effector-encoding genes, the LetA-RsmYZ-CsrA cascade also controls the expression of regulators that by themselves might regulate the expression of other effector-encoding genes.…”
Section: Resultsmentioning
confidence: 68%
“…2A and B, respectively). It should be noted that FleR and LqsR were previously suggested to be involved in flagellum gene expression (57,58) and that LqsR was also suggested to be involved in the regulation of effector-encoding genes (58). These results show that, in addition to directly contributing to the regulation of effector-encoding genes, the LetA-RsmYZ-CsrA cascade also controls the expression of regulators that by themselves might regulate the expression of other effector-encoding genes.…”
Section: Resultsmentioning
confidence: 68%
“…The response regulator LqsR contributes to virulence processes such as phagocytosis and the formation of the LCV by relaying signals from the adjacent sensor kinase LqsS (334,335). Neighboring this system is an autoinducer synthase, LqsA, which was recently shown to synthesize 3-hydroxypentadecan-4-one, the small Legionella autoinducer 1 (LAI1) (313).…”
Section: The Biphasic Replicative Cycle Of L Pneumophilamentioning
confidence: 99%
“…Bruggemann and co-workers examined the transcriptomic changes for the transmissive phase relative to the replicative phase of L. pneumophila Colby strain and found that tsp was up-regulated 54-fold (Bruggemann et al, 2006). Secondly, the Lqs (Legionella quorum sensing) gene is a key transcriptional activator for the transmissive phase and lqs mutants were found to have lower levels of tsp mRNA and protein (Tiaden et al, 2008). Tsp (tail-specific protease) was first identified from E. coli as a periplasmic serine protease which selectively degrades proteins with specific hydrophobic C-terminal sequences (Silber et al, 1992;Keiler and Sauer, 1995), impacting on cell division and morphology during stress (Hara et al, 1991), and has also been implicated in potentiating long-chain fatty acid transport in E. coli (Azizan and Black, 1994).…”
Section: Introductionmentioning
confidence: 99%